EVALUATION OF THE ACCURACY OF DIFFERENT GNSS DEVICES - Araújo, G. M.; Santos, F. F. L.; Martins, R. N.; Tavares, L. C. M.; Viana, L. A.; Almeida, S. L. H. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The use of GNSS (Global Navigation Satellite System) devices for applications in agricultural, civil construction, aeronautics and automobile fields have been gaining increasing prominence in the global scenario. The use of this technology enables a more accurate and practical approach to the problems encountered by mankind. To this end, accuracy in position measurement is of paramount importance for the precise management of any activity. In order to compare the accuracy of different types of receivers (GPS Navigation device, GPS Navigation in smartphone device and Topographic GPS), this work consisted in the accomplishment of three different tests of accuracy of positioning (tests of height, alignment and area) front to a reference measurement (measuring tape), in order to evaluate the applicability of these devices in operations that demand high precision. It was concluded that the Topographic GPS obtained the best performance of all the tested devices. However, none of the receivers presented satisfactory results to be used in operations that demand high precision.